Correlation Of Erythrocyte Sedimentation Rate (ESR) and Lymphocyte Counts in Pulmonary Tuberculosis Patients during Intensive Treatment in Purwokerto City - Eko Naning Sofyanita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Pulmonary tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis which most often attacks the lungs by spreading through the air in patients who cough, sneeze or spit. In tuberculosis, the erythrocyte sedimentation rate examination is used to help diagnose the course of the disease and help for the success of chronic therapy, and the examination of the lymphocyte count is used to support the diagnosis of bacterial infection. This study is an analytic study through a cross-sectional approach with the Pearson Correlation test. The results of this LED examination were 8 samples (21%) normal and 30 samples (79%) abnormal. On examination of the lymphocyte count, 21 samples (55%) had lymphopenia, 16 samples (42%) were normal patients, and 1 sample (3%) had lymphocytosis. In the Pearson correlation test, the correlation is unidirectional but moderately or moderately correlated (r=0.304). Based on these results, it can be concluded that there is a relationship between erythrocyte sedimentation rate and lymphocyte count. This means that if the LED value is large, the number of lymphocytes will also increase.